2004
DOI: 10.1109/tasc.2004.829065
|View full text |Cite
|
Sign up to set email alerts
|

Study of time dependent magnetic field variation due to current redistribution in Rutherford cable

Abstract: Time-varying magnetic field quality of superconducting accelerator magnets is a important issue of accelerator operation at particle injection. This is induced by magnetization changes of superconductors due to redistributions of imbalance current of superconducting strands in cables. Because the imbalance current and its redistributions induce time variations of magnetic periodic patterns, to clarify the mechanism of time-varying magnetic field, we performed periodic pattern measurements on quadrupole magnets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…It is found that the measured magnetic field on the HTS tape shows a logarithmic increase with time. This finding seems to be very similar to the well-known logarithmic decays of magnetization observed in HTS bulk superconducting materials as well as in NbTi Rutherford cables [12].…”
Section: Investigation Of the Mechanism Of Additional Loss Generatsupporting
confidence: 88%
“…It is found that the measured magnetic field on the HTS tape shows a logarithmic increase with time. This finding seems to be very similar to the well-known logarithmic decays of magnetization observed in HTS bulk superconducting materials as well as in NbTi Rutherford cables [12].…”
Section: Investigation Of the Mechanism Of Additional Loss Generatsupporting
confidence: 88%